Ball-and-chain inactivation in a calcium-gated potassium channel - Fan, Chen (Nature, 2020)
Inactivation is the process by which ion channels terminate ion flux through their pores while opening stimulus is still present(1). In neurons, inactivation of both sodium and potassium channels is crucial for action potential generation and regulation of firing frequency(1,2). It has been proposed that a cytoplasmic domain of either the channel or an accessory subunit plugs the open pore to inactivate the channel via a “ball-and-chain” mechanism(3–7), but no structural evidence of this has been observed to date. Here, we used cryo-electron microscopy to determine the molecular gating mechanism in calcium-activated potassium channels by obtaining structures of a purely calcium-gated and inactivating channel in a lipid environment. In the absence of Ca(2+) we obtained one structure in closed state, shown by atomistic simulations to be highly flexible in lipid bilayers at ambient temperature, with large rocking motions of the gating ring and bending of pore-lining helices. In Ca(2+)-bound conditions, we obtained several structures including multiple open-inactivated conformations, further indication of a very dynamic protein. These different channel conformations are distinguished by rocking of the gating rings with respect to the transmembrane region, indicating symmetry breakage across the channel. Furthermore, in all conformations displaying open channel pores, the N-terminus of one subunit of the channel tetramer sticks into the pore and plugs it, a strong interaction as shown by free energy simulations. Deletion of this N-terminus leads to functionally non-inactivating channels and structures of open states without pore-plug, indicating that this previously unresolved N-terminal peptide is responsible for a ball-and-chain type inactivation mechanism.